2023
DOI: 10.1001/jamapediatrics.2022.4885
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Revisits at US Pediatric Emergency Departments

Abstract: ImportancePediatric emergency department (ED) visits for mental health crises are increasing. Patients who frequently use the ED are of particular concern, as pediatric mental health ED visits are commonly repeat visits. Better understanding of trends and factors associated with mental health ED revisits is needed for optimal resource allocation and targeting of prevention efforts.ObjectiveTo describe trends in pediatric mental health ED visits and revisits and to determine factors associated with revisits.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In Reply We thank Carlson et al for their interest in our study . We agree with the need to accurately identify patients with behavioral outbursts to allow for further study of this important population.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In Reply We thank Carlson et al for their interest in our study . We agree with the need to accurately identify patients with behavioral outbursts to allow for further study of this important population.…”
supporting
confidence: 56%
“…Use of administrative data is inherently limited by the accuracy of diagnoses assigned by clinicians and by patient cohort definitions . Validated systems such as the Child and Adolescent Mental Health Disorders Classification System, which was used in our study, can help with phenotyping and identification of mental health patient cohorts, but need to be continually improved . The future adoption of International Classification of Diseases , 11th Revision provides an opportunity to further refine diagnosis codes pertaining to mental health conditions to improve their accuracy and usability.…”
mentioning
confidence: 99%
“…To the Editor The importance of impulse control disorders and social determinants of health in predicting emergency department visits for children, as reported by Cushing et al, further highlights the impact of impairing emotional outbursts on pediatric mental health. We recently found that, for 435 comprehensive psychiatric emergency program (CPEP) encounters for 339 children aged 5 to 12 years over a 9-month period, 22% were revisits and 28% were brought in by police .…”
mentioning
confidence: 94%
“…Impairing emotional outbursts, characterized by extreme distress, agitation, and sometimes suicidal threats, are transdiagnostic and are not captured by 1 diagnosis. Cushing et al state that episodes of agitation may account for the emergency department revisits. They absolutely might.…”
mentioning
confidence: 99%
“…We agree that co-occurring substance use disorders, developmental disabilities, and physical health conditions exacerbate challenges in access to mental health services. Children with neurodevelopmental disorders, such as autism spectrum disorder, are more likely to revisit the emergency department for mental health conditions and are more likely to experience boarding (prolonged emergency department or inpatient stays awaiting mental health services) . Additionally, children with eating disorders may face challenges in accessing specialized services, as visits for these conditions have increased during the COVID-19 pandemic .…”
mentioning
confidence: 99%